Engaging Media with Medical Institutions: Experience from Tertiary Hospital in Eastern India - Parida, Swayam Pragyan; Bhatia, Vikas; Sinha, Sonali; Giri, Prajna Paramita; Kumar Behera, Binod (Indian Journal of Community Health, 2020)
Behaviour change is an important aspect of the successful implementation of any national health program. Social behaviour change among end-user can be possible by imparting the right information in the right quantity to the right audience, at frequent intervals through the proper medium. Mass media, both electronic and print are considered useful modes to deliver all public health-related messages to the people. However, the key is to provide correct information to the media for dissemination. On the other hand, medical colleges have a depth of knowledge on technical know-how but reaching a larger population is quite challenging. Therefore, a team approach should be planned by establishing a partnership between media and medical colleges and then the social behaviour change can be achieved in the desired direction. In lieu of this novel partnership, the Department of Community Medicine and Family Medicine, All India Institute of Medical Sciences Bhubaneswar had taken the initiative to bring together media personnel and faculty of medical colleges to chalk and roll out the behaviour change communication for nutrition interventions. This program was highly successful as the liaison helped disseminate the right information to the people. Also, the faculty and residents gained insight into dealing with media and thereby serving the community.